High structure acetylene black, production method thereof, composition and application thereof

By incompletely burning the acetylene-containing hydrocarbon raw material in contact with oxygen in the reactor, high-structure acetylene black was prepared, which solved the shortcomings in the uniform incorporation of acetylene black in the material and the realization of low-concentration conductivity in the prior art, and achieved efficient and economical electrical conductivity and thermal conductivity imparting the material.

CN119768475APending Publication Date: 2025-04-04ORION ENGINEERED CARBONS IP GMBH & CO KG
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380062362.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-23
Filing Date
2023-08-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing acetylene black is difficult to incorporate uniformly into the material when making plastic or rubber products or preparing aqueous or solvent-based compositions, and does not perform well when achieving the desired level of conductivity at lower concentrations.

Method used

By providing the reactor with acetylene-containing hydrocarbon feedstock and oxygen-containing gas, contacting them and achieving incomplete combustion, a high-structure acetylene black has an oil absorption value of 360 mL/100 g and a BET surface area of ​​50 m2/g to 200 m2/g.

Benefits of technology

The required electrical and thermal conductivity at relatively low acetylene black content is achieved, and performs well in processing and application performance, and maintains high purity acetylene black properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119768475A_ABST
    Figure CN119768475A_ABST
Patent Text Reader

Abstract

The present invention provides a high structure acetylene black having an oil absorption (OAN) of 360 mL / 100 g or more and a BET surface area in the range of 50 m2 / g to 200 m2 / g. Such high structure carbon black exhibits excellent electrical conductivity and good process properties, such as dispersibility, with superior ability to impart electrical conductivity and / or thermal conductivity to various materials, making them particularly suitable for various applications that require or are beneficial to high electrical conductivity and (or) thermal conductivity, as well as for use in the field of electronic devices. The present invention relates to the manufacture of conductive and / or thermally conductive materials, such as electrodes and other components of energy storage and / or energy conversion devices, or conductive and / or thermally conductive materials and articles made therefrom.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a novel high-structure acetylene black, its production, including an acetylene black composition and a product made thereof, and the use and application of acetylene black, such as being used for producing electrodes or other components of energy storage devices or energy conversion devices, or for rubber or plastic products. Background Art

[0002] Acetylene black is a special type of carbon black. Acetylene black is usually produced by thermal decomposition of acetylene gas or hydrocarbon feedstock containing acetylene at high temperature to form colloidal carbon black particles and hydrogen, as described in J.-B. Donnet et al., "Carbon Black: Science and Technology", second edition. Other manufacturing methods, such as described in US4013759, are based on incomplete combustion of hydrocarbon feedstock. Acetylene black is usually very pure (carbon content is usually higher than 99% by weight) and exhibits good intrinsic conductivity. These characteristics make acetylene black particularly interesting compared to other types of carbon black (such as furnace black) and are suitable for applications requiring high purity and good electrical or thermal conductivity. Therefore, they are widely used in the production of electrodes, batteries, fuel cells, capacitors or heating elements and for providing antistatic properties, heat dissipation or electrical conductivity, for example, plastic or rubber materials and products, such as tires and components thereof (such as tire airbags), cables, conveyor belts, rollers, hoses, floors or shoes, or for electronic components, paints, ink coatings and adhesives. However, the types of acetylene black available are limited. In addition, for example, when manufacturing plastic or rubber products or preparing aqueous or solvent-based compositions (for example, for the manufacture of electrodes, coatings, paints or inks), it is difficult to uniformly incorporate them into materials (for example, plastic or rubber materials) or liquid carrier media. This can also have an adverse effect on the conductivity that can be achieved by the acetylene black doped material obtained. Therefore, there is a continuous pursuit and demand for acetylene black that exhibits enhanced conductivity and good process properties (for example, dispersibility) and has a superior ability to impart conductivity and / or thermal conductivity to various materials (for example, allowing the desired material conductivity level to be achieved at a lower concentration of acetylene black), thereby saving costs, ideally without adversely affecting other properties of acetylene black related to the intended application, and can be achieved in a cost-effective manner using readily available raw materials and equipment.

[0003] It is therefore an object of the present invention to provide an acetylene black that overcomes or reduces at least some of the above-mentioned deficiencies and limitations of the prior art. Specifically, it is an object to provide an acetylene black that exhibits enhanced conductivity and can be effectively incorporated into various materials to impart the desired conductivity at relatively low levels. Such acetylene black should be obtained in an economical manner that does not adversely affect other beneficial properties of acetylene black (e.g., high purity). Summary of the invention

[0004] The above object is achieved by providing a novel high-structure acetylene black as defined in the appended independent claim 1 according to the present invention.

[0005] The acetylene black according to the present invention is characterized by having an oil absorption value (OAN) of more than 360 mL / 100 g and a range of 50 m / s. 2 / g to 200m 2 / g of BET surface area.

[0006] The present invention also relates to a method for preparing the acetylene black of the present invention. The method comprises providing a hydrocarbon feedstock containing acetylene to a reactor, providing an oxygen-containing gas to the reactor, achieving incomplete combustion of the hydrocarbon feedstock containing acetylene by contacting the hydrocarbon feedstock containing acetylene with the oxygen-containing gas, thereby forming acetylene black in the reactor, and recovering the formed acetylene black. The hydrocarbon feedstock containing acetylene and the oxygen-containing gas are introduced into the reactor so that the molar ratio of oxygen to acetylene is in the range of 0.30 to 0.80.

[0007] The present invention also relates to compositions, such as electrode compositions and rubber compositions or plastic compositions, comprising the inventive acetylene black material disclosed herein.

[0008] The present invention also relates to articles made of the acetylene black or composition of the present invention, in particular electrodes or other components of energy storage and / or conversion devices, and rubber products or plastic products. The present invention also relates to energy storage and / or conversion devices comprising electrodes or components made of the acetylene black or composition of the present invention.

[0009] In addition, the present invention relates to the use of the acetylene black material disclosed herein as a conductive agent, antistatic agent, thermal conductor, reinforcing filler and / or colorant, for example, for the production of electrodes and other components of energy storage and / or energy conversion devices (such as primary batteries, secondary batteries, fuel cells and capacitors), and / or plastic products made of thermoplastic or thermosetting polymers or rubber matrices (such as tires or components thereof, wires, cables and their sheaths, belts, hoses, soles, rollers, heaters or airbags (such as tire airbags), thermal conductive materials, heat transfer materials, and / or in coatings, paints or inks.

[0010] The acetylene black according to the present invention exhibits very high intrinsic conductivity and has a strong ability to impart electrical conductivity and / or thermal conductivity to various materials, such as allowing the desired material conductivity level to be achieved at relatively low acetylene black concentrations. They can be effectively incorporated into materials to provide compositions with good processability and application properties, including, for example, electrode compositions. In addition, the acetylene black according to the present invention can maintain or even enhance other beneficial properties of acetylene black (e.g., high purity), and can be obtained in an economical manner using readily available raw materials and equipment.

[0011] These and other optional features and advantages of the present invention will be described in more detail in the following description. DETAILED DESCRIPTION

[0012] As used herein, the term "comprising" should be understood as open ended and does not exclude the presence of additional undescribed or unlisted elements, materials, components, method steps, etc. The terms "including," "containing," and similar terms should be understood as synonymous with "comprising." As used herein, the term "consisting of" should be understood to exclude the presence of any unspecified elements, components, method steps, etc.

[0013] As used herein, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise.

[0014] Unless otherwise indicated, the numerical parameters and ranges set forth in the following specification and the appended claims are approximate values. Although the numerical ranges and parameters setting forth the broad scope of the invention are approximate values, the numerical values ​​set forth in the specific embodiments are recorded as accurately as possible. However, any numerical value necessarily contains errors caused by the standard deviation in the respective measurements.

[0015] In addition, it should be understood that any numerical range recited herein is intended to include all subranges contained therein. For example, a range of "1 to 10" is intended to include any and all subranges between the recited minimum value 1 and the recited maximum value 10, i.e., all subranges starting with equal to or greater than the minimum value 1 and ending with equal to or less than the maximum value 10, and all subranges in between, such as 1 to 6.3 or 5.5 to 10 or 2.7 to 6.1.

[0016] Unless otherwise specified, all parts, quantities, concentrations, etc. mentioned herein are by weight.

[0017] As mentioned above, the acetylene black according to the present invention is characterized by having a medium BET surface area, i.e. in the range of 50 m 2 / g to 200m 2 / g BET surface area. The acetylene black of the present invention may have, for example, 50 m 2 / g or more BET surface area, for example 60m 2 / g or above, or 70m 2 / g or above, or 80m 2 / g or above, or 90m 2 / g or more, or 100m 2 Above, or 110m 2 Above, or 120m 2 / g or above, or 130m 2 / g or more. The acetylene black of the present invention may have, for example, 200 m 2 / g or less, for example, 190m 2 / g or less, or 180m 2 / g or less, or 170m 2 / g or less, or 160m 2 / g or less, or 150m 2 Below, or 140m 2 The BET surface area of ​​the acetylene black of the present invention may be within any range between the values ​​described, for example, 50 m 2 / g to 200m 2 / g, or 60m 2 / g to 180m 2 / g, or 80m 2 / g to 160m 2 / g. Preferably, the BET surface area of ​​the acetylene black of the present invention is 100m 2 / g to 200m 2 / g, more preferably in the range of 120m 2 / g to 200m 2 / g, even more preferably in the range of 130 m 2 / g to 180 m² / g, and more preferably 130 m² / g. 2 / g to 160m 2 The "BET surface area" used herein refers to the BET surface area which can be measured by nitrogen adsorption according to ASTM D6556-19a, as also used in the Examples.

[0018] As described above, in addition, the acetylene black according to the present invention is characterized in that it has a high structure. In the field of carbon black materials, structure refers to the degree to which a single primary carbon black particle fuses to form a larger aggregate consisting of a plurality of primary carbon black particles. The oil absorption value can be used as an indicator of structure. Therefore, the acetylene black according to the present invention has a high oil absorption value (OAN), which indicates the high structure of acetylene black. The acetylene black of the present invention has an oil absorption value (OAN) of more than 360 mL / 100 g. The acetylene black of the present invention can, for example, have an OAN of more than 370 mL / 100 g, for example, more than 380 mL / 100 g, or more than 390 mL / 100 g, or more than 400 mL / 100 g, or more than 410 mL / 100 g. The acetylene black of the present invention may, for example, have an OAN of up to 600 mL / 100 g, such as 550 mL / 100 g or less, or 500 mL / 100 g or less, or 490 mL / 100 g or less, or 480 mL / 100 g or less, or 470 mL / 100 g or less, or 460 mL / 100 g or less, or 450 mL / 100 g or less. The OAN of acetylene black may be in a range between any of the values ​​recited, such as 360 mL / 100 g to 600 mL / 100 g, or 380 mL / 100 g to 500 mL / 100 g, or 410 mL / 100 g to 450 mL / 100 g. Preferably, the OAN value is in the range of 380 mL / 100 g to 500 mL / 100 g, more preferably in the range of 410 mL / 100 g to 450 mL / 100 g. As used herein, "Oil Absorption Number (OAN)" refers to the oil absorption value that can be measured according to ASTM D2414-19, as also used in the Examples.

[0019] As described above, the acetylene black according to the present invention exhibits very high intrinsic conductivity and can be effectively incorporated into various materials, and has a strong ability to impart electrical conductivity and / or thermal conductivity to various materials. Without intending to be limited by any theory, it can be believed that the characteristics of the acetylene black of the present invention (such as high structure and appropriate specific surface area) can be particularly conducive to the formation of conductive paths and networks, and promote interaction with more or less polar components (such as aqueous or organic solvent-based carrier media, plastic materials or electrolytes).

[0020] In addition to the above-mentioned structure and BET surface area, the acetylene black of the present invention may also have one or more or all of the characteristics described below.

[0021] Therefore, the acetylene black according to the present invention can be characterized, for example, by the oil absorption value (COAN) of the compressed sample determined according to ASTM D3493-19a. The COAN can be, for example, in the range of 30% or more (e.g., 40% or more) of the OAN value to the OAN value of the acetylene black. The acetylene black can, for example, have a COAN of 150 mL / 100 g or more, for example, 170 mL / 100 g or more, or 180 mL / 100 g or more. The acetylene black can, for example, have a COAN of 300 mL / 100 g or less, for example, 250 mL / 100 g or less, or 200 mL / 100 g or less. The COAN of acetylene black can be in the range between any of the values ​​described, for example, 150 mL / 100 g to 300 mL / 100 g, or 170 mL / 100 g to 250 mL / 100 g.

[0022] In addition, as mentioned above, acetylene black generally includes agglomerates of multiple smaller particles, which are referred to as "primary particles". Agglomerates can be, for example, aggregates of multiple primary acetylene black particles fused together at their contact points and cannot be easily separated. The size of the primary particles in acetylene black may vary. The average primary particle size of the acetylene black material can be determined by TEM image analysis according to ASTM D3849-07. The acetylene black according to the present invention can, for example, have an average primary particle size of more than 10 nm, for example, more than 12 nm, or more than 14 nm, or more than 16 nm, or more than 18 nm. The average primary particle size of the acetylene black according to the present invention can, for example, be less than 30 nm, for example, less than 28 nm, or less than 26 nm, or less than 24 nm. The average primary particle size of the acetylene black of the present invention can be in the range between any of the values ​​described, for example, 10 nm to 30 nm, or 14 nm to 28 nm, or 16 nm to 24 nm.

[0023] The acetylene black of the present invention may include aggregates that may have an irregular shape or a non-spherical shape. The shape may be characterized, for example, by an aspect ratio defined as the ratio of the minimum Feret diameter to the maximum Feret diameter. The powdered acetylene black particles of the present invention may, for example, have an aspect ratio less than 0.8, such as less than 0.6, or less than 0.5, or less than 0.3. The aspect ratio may be determined by averaging at least 50 particles by electron microscope images. The irregular or non-spherical shape of the particles may be beneficial to forming conductive paths and networks.

[0024] Additionally or alternatively, acetylene black according to the present invention can be characterized by void volume. Void volume can be measured according to ASTM D7854-18a by the compression volume of the acetylene black weighing sample in a cylindrical chamber (the compression volume is a function of the pressure applied by the movable piston). The measurement method is described in more detail in the following experimental section. Void volume provides a way to evaluate the structure of acetylene black at different densities and levels of aggregate reduction. The increase in the irregularity and non-sphericity of the aggregates can lead to compression resistance, and is therefore usually reflected by a higher void volume value. Void volume is usually reported with a void volume value obtained at a specific mean geometric pressure (e.g., 50MPa, 75MPa, or 125MPa). Acetylene black according to the present invention can, for example, have a 60cm2 value measured at an average geometric pressure of 50MPa. 3 / 100g or more void volume, e.g. 70cm 3 / 100g or more, 75cm 3 / 100g or more, or 80cm 3 / 100g or more. The acetylene black according to the present invention may, for example, have a carbon content of 120 cm2 measured at an average geometric pressure of 50 MPa. 3 / Void volume below 100g, for example 100cm 3 / 100g or less, or 90cm 3 / 100g or less. The void volume (at 50 MPa) can be in the range between any of the values ​​listed, for example, 60 cm 3 / 100g to 120cm 3 / 100g, or 75cm 3 / 100g to 100cm 3 / 100g. Additionally or alternatively, the acetylene black according to the present invention may have a 50cm3 / cm2 average geometric pressure measured at 75MPa. 3 / 100g or more void volume, e.g. 60cm 3 / 100g or more, or 65cm 3 / 100g or more, or 65cm 3 / 100g or more. The acetylene black according to the present invention may, for example, have a 100cm 3 / Void volume below 100g, for example 90cm 3 / 100g or less, or 80cm 3 / 100g or less. The void volume (under 75 MPa) can be in the range between any of the values ​​listed, for example, 50 cm 3 / 100g to 100cm 3 / 100g, or 65cm 3 / 100g to 80cm3 / 100g. In addition, or alternatively, the acetylene black according to the present invention may have a mean geometric pressure of 125MPa and a relative humidity of 40cm 3 / 100g or more void volume, e.g. 45cm 3 / 100g or more, or 50cm 3 / 100g or more. The acetylene black according to the present invention may, for example, have a carbon content of 80 cm2 measured at an average geometric pressure of 125 MPa. 3 / 100g or less void volume, e.g. 70cm 3 / 100g or less, or 60cm 3 The void volume (under 125 MPa) can be within any range between the values ​​reported, for example, 40 cm 3 / 100g to 80cm 3 / 100g, or 50cm 3 / 100g to 60cm 3 / 100g.

[0025] Additionally or alternatively, the acetylene black material according to the present invention can be characterized by its aggregate size distribution. The aggregate size distribution can be determined using a disc centrifuge photosedimentometer (DCP) according to ISO 15825:2017. In particular, the mode value (D mode The aggregate size distribution is described by the mass distribution curve (i.e., the diameter of the aggregate that occurs most frequently, which appears as a peak on the mass distribution curve). The aggregate size distribution can be further described by the width of the mass distribution curve measured at the half-maximum modulus (ΔD50), which is a measure of the width of the aggregate size distribution. For example, acetylene black according to the present invention may have D mode Aggregate size distribution above 50 nm, for example, D mode 60 nm or more, or 70 nm or more, or 80 nm or more. The acetylene black according to the present invention may have, for example, D mode The aggregate size distribution is below 200 nm, for example, D mode 150nm or less, or 130nm or less, or 120nm or less. mode The range may be between any of the values ​​recited, for example 50 nm to 200 nm, or 70 nm to 150 nm. Alternatively or additionally, the aggregate size distribution of the acetylene black according to the present invention may exhibit a ratio ΔD50 / D50 of 0.5 or more. mode, for example, 0.6 or more, or 0.7 or more, or 0.8 or more, or 0.9 or more, or 1.0 or more, or 1.2 or more, or 1.5 or more. The aggregate size distribution of acetylene black may, for example, have a ratio ΔD50 / D of at most 2.5. mode , for example, less than 2.2, or less than 2.0, or less than 1.8, or less than 1.7. Ratio ΔD50 / D mode Ranges between any of the recited values ​​are possible, for example 0.5 to 2.5, or 1.0 to 2.0, or 1.5 to 2.0.

[0026] In addition, the acetylene black according to the present invention can be characterized by the amount of grit. Grit refers to coarse particles that are generally undesirable because they may have an adverse effect on the application performance of the acetylene black material. The acetylene black according to the present invention can have a lower amount of grit. For example, based on the gross weight of the acetylene black, it can have less than 100 ppm of residues that may not pass through an ASTM sieve (sieve size of 45 μm (ASTM E11-17, sieve target number: #325)), more preferably less than 50 ppm or less than 10 ppm.

[0027] Additionally or alternatively, acetylene black according to the present invention may exhibit a relatively high degree of crystallinity and / or a relatively high proportion of graphitic domains, as may be shown by Raman spectroscopy. The Raman spectrum of the carbon black material includes a peak at about 1360 cm -1 and about 1580cm -1 At about 1360cm -1 The "D band" at about 1580 cm is usually attributed to disordered sp² carbon atoms, while -1 The "G band" at is attributed to the sp² carbon atoms or ordered sp² carbon atoms of graphite. Therefore, the ratio of the integrated area of ​​the "D band" to the integrated area of ​​the "G band" (D / G ratio) provides a measure of the crystallinity and / or proportion of the graphite domain, and the lower the D / G ratio, the higher the order / crystallinity of the graphite domain in the carbon black material studied and / or the higher the proportion of the graphite domain. The acetylene black of the present invention can show a D / G ratio of less than 1.5 measured by Raman spectroscopy, preferably less than 1.4, more preferably less than 1.3. The acetylene black of the present invention can have a D / G ratio as low as 0.8, such as more than 0.9, or more than 1.0. The acetylene black of the present invention can have a D / G ratio in the range between any of the recorded values, such as 0.8 to 1.5, or 0.9 to 1.4, or 1.0 to 1.3.

[0028] Additionally or alternatively, the acetylene black according to the present invention may be characterized by its grain size. Acetylene black may be characterized, for example, by its L cThe acetylene black of the present invention may have a L crystallite size of more than 26 Å, for example. c The acetylene black of the present invention may have a L grain size of, for example, 28 Å or more, or 30 Å or more, or 32 Å or more. c The crystallite size is, for example, 45 Å or less, or 40 Å or less, or 38 Å or less, or 35 Å or less. The acetylene black of the present invention may have an L in the range between any of the values ​​recited. c The crystallite size is, for example, 26 Å to 50 Å, or 28 Å to 40 Å, or 30 Å to 38 Å. Alternatively or additionally, the acetylene black of the present invention may be prepared, for example, by L a Acetylene black can, for example, have a L a The crystallite size is, for example, 65 Å or more, or 70 Å or more, or 75 Å or more. Acetylene black may, for example, have an L of 100 Å or less. a The crystallite size is, for example, 95 Å or less, or 90 Å or less. The acetylene black of the present invention may have an L in the range between any of the values ​​recited. a The crystallite size is, for example, 60 Å to 100 Å, or 70 Å to 90 Å. L can be determined by X-ray diffraction as described, for example, in "Self-decomposition of hydrogenperoxide on the surface of dispersed carbon black", GI Razdyakonova, VALikholobov, Nanosystems, RENSIT, 2015, 7(2): 180-190. c Grain size and L a Grain size.

[0029] Additionally or alternatively, the acetylene black of the present invention can be characterized by its chemical composition or purity, for example, by one, multiple or all of the following: its carbon content, oxygen content, hydrogen content, sulfur content, nitrogen content, total metal content and / or ash content. Typically, acetylene black has a high carbon content and is essentially composed of carbon. Therefore, based on the gross weight of acetylene black, the acetylene black of the present invention can have a carbon content of more than 98.5 wt %, preferably more than 99.0 wt %, or more than 99.2 wt %, or more than 99.4 wt %, or more than 99.5 wt %, or more than 99.6 wt %, for example, up to about 100 wt %. Therefore, the content of non-carbonaceous impurities (if any) may be very low. Based on the gross weight of acetylene black, acetylene black can, for example, have a hydrogen content of less than 1.0 wt %, for example, less than 0.5 wt %, or less than 0.3 wt %. Based on the gross weight of acetylene black, the acetylene black of the present invention can, for example, have an oxygen content of less than 0.1 wt %, for example, less than 0.05 wt %, or less than 0.03 wt %. Based on the gross weight of acetylene black, the acetylene black of the present invention can, for example, have a nitrogen content of less than 0.2 wt %, for example, less than 0.1 wt %. Based on the gross weight of acetylene black, the acetylene black of the present invention can, for example, have a sulfur content of less than 0.1 wt %, for example, less than 0.05 wt %, or less than 0.01 wt %. The carbon content, oxygen content, hydrogen content, sulfur content and nitrogen content of acetylene black can be determined by quantitative elemental analysis. Additionally or alternatively, the acetylene black of the present invention has a low content of metal. Based on the gross weight of acetylene black, acetylene black can, for example, have a metal content of less than 1000 ppm, for example, less than 100 ppm, or less than 50 ppm, or less than 20 ppm, or less than 10 ppm. The metal of acetylene black can be determined, for example, by inductively coupled plasma optical emission spectroscopy (ICP-OES) using a Prodigy 7 instrument purchased from TELEDYNE LEEMAN LABS, USA. In addition, based on the total weight of acetylene black, the acetylene black of the present invention can have an ash content of 1 wt % or less, such as 0.5 wt % or less, or 0.2 wt % or less, or preferably 0.1 wt % or less, or more preferably 0.05 wt % or less. The ash content can be determined according to ASTM D1506-15.

[0030] It has been found that acetylene black according to the present invention has extremely high electrical conductivity. Acetylene black according to the present invention may, for example, exhibit low powder resistivity. The powder resistivity may be determined, for example, by measuring the resistance of a powder sample of acetylene black using a void volume tester that can simultaneously measure resistance as described in the examples, which is compressed in a chamber at a defined average geometric pressure. Acetylene black according to the present invention may, for example, have a powder resistivity of less than 1.0 Ω·cm measured at a pressure of 50 MPa, such as 0.5 Ω·cm or less, or 0.3 Ω·cm or less, or 0.2 Ω·cm or less, or 0.1 Ω·cm or less, or 0.08 Ω·cm or less, or 0.06 Ω·cm or less. It may, for example, have a powder resistivity of more than 0.005 Ω·cm measured at a pressure of 50 MPa, such as more than 0.01 Ω·cm, such as more than 0.02 Ω·cm, or more than 0.03 Ω·cm. The acetylene black of the present invention may have a powder resistivity (at 50 MPa) ranging between any of the recited values, for example, 0.005 Ω·cm to 1.0 Ω·cm, or 0.01 Ω·cm to 0.1 Ω·cm, or 0.02 Ω·cm to 0.06 Ω·cm.

[0031] As described herein, acetylene black according to the present invention can be produced based on the incomplete combustion of an acetylene-containing hydrocarbon feedstock in an oxygen-containing gas. This incomplete combustion reaction can be schematically represented by the following formula:

[0032] C2H2+ x O2→ 2(1-x) C + 2x CO + H2

[0033] Wherein x is a value greater than 0 and less than 1. As described above, the present invention therefore also relates to a method for producing acetylene black. The method comprises providing a hydrocarbon feedstock containing acetylene to a reactor, providing an oxygen-containing gas to the reactor, achieving incomplete combustion of the hydrocarbon feedstock containing acetylene by contacting the hydrocarbon feedstock containing acetylene with the oxygen-containing gas, thereby forming acetylene black in the reactor, and recovering the formed acetylene black. The amount of the hydrocarbon feedstock containing acetylene and the oxygen-containing gas introduced into the reactor is controlled so that the molar ratio of oxygen to acetylene [represented by x in the above formula] is in the range of 0.30 to 0.80. Preferably, the molar ratio of oxygen to acetylene is in the range of 0.30 to 0.60, more preferably 0.32 to 0.50, for example 0.35 to 0.45, or 0.37 to 0.42.

[0034] The hydrocarbon feedstock used in the method according to the present invention comprises acetylene. It may optionally further comprise one or more hydrocarbons except acetylene. Such optional additional hydrocarbons may be exemplified by, but not limited to, olefinically unsaturated hydrocarbons (such as olefins (alkylenes) (such as ethylene or propylene), aromatic hydrocarbons (such as benzene, toluene or xylene), aliphatic hydrocarbons (such as alkanes (such as methane, ethane or propane)), or a mixture or combination of any of the above hydrocarbons. Typically, based on the gross weight of the hydrocarbon feedstock, the hydrocarbon feedstock comprises at least 50% by weight of acetylene, for example, 70% by weight or more, or 80% by weight or more, or 90% by weight or more, or 95% by weight or more, or 98% by weight or more, or 99% by weight or more of acetylene. Preferably In some embodiments, the hydrocarbon feedstock is composed of acetylene. For the sake of clarity, the hydrocarbon feedstock composed of acetylene can still contain impurities commonly found in industrial acetylene gas, such as impurities with a content of up to 2% by weight based on the gross weight of the hydrocarbon feedstock. The acetylene from the acetylene recovery unit of the steam cracking unit is usually received with a purity of ≥99% by weight. The hydrocarbon feedstock containing acetylene is usually provided to the reactor in a gaseous form. Alternatively, the hydrocarbon feedstock can be preheated before it contacts the oxygen-containing gas. If preheating is performed, the hydrocarbon feedstock containing acetylene is usually preheated to a temperature below 150° C. for safety reasons.

[0035] Can use any oxygen-containing gas such as but not limited to air, oxygen-enriched air, nitrogen-enriched air, oxygen-containing process gas mixture (for example, tail gas from carbon black production) or oxygen itself as oxygen-containing gas.Based on the cumulative volume of oxygen-containing gas, oxygen-containing gas can for example contain more than 1 volume % oxygen, or more than 5 volume %, for example more than 10 volume %, or more than 15 volume %, or more than 20 volume %.Based on the cumulative volume of oxygen-containing gas, oxygen-containing gas can for example contain up to 100 volume % oxygen, for example below 99 volume %, or below 95 volume %, or below 90 volume %, or below 80 volume %, or below 60 volume %, or below 50 volume %, or below 40 volume %, or below 30 volume %.Based on the cumulative volume of oxygen-containing gas, oxygen-containing gas can have the oxygen content of the scope between any numerical value recorded, for example 1 volume % to 100 volume %, for example 10 volume % to 80 volume %, or 20 volume % to 30 volume %.Due to economic reasons, preferably use air as the oxygen-containing gas in the method according to the present invention. The oxygen-containing gas may optionally be preheated before contacting it with the hydrocarbon feedstock. For example, the oxygen-containing gas may be preheated to a temperature above 200° C., such as above 300° C., or above 500° C., or above 700° C. For practical reasons, the oxygen-containing gas is not usually preheated to a temperature above 850° C.

[0036] As described, for example, in US4013759, an optionally preheated oxygen-containing gas and a hydrocarbon feedstock are supplied to a reactor by an introduction device (e.g., a burner) so that they contact each other for incomplete combustion of the hydrocarbon feedstock, thereby forming acetylene black in the reactor. In the method disclosed herein, the rate at which the oxygen-containing gas and the hydrocarbon feedstock are supplied to the reactor is generally controlled so that the molar ratio of oxygen to acetylene is within the above range. The rate at which the oxygen-containing gas and the hydrocarbon feedstock are supplied to the reactor can be, for example, independently 5 Nm / s, respectively. 3 / h to 500Nm 3 / h range, for example 10Nm 3 / h to 300Nm 3 / h, or 20Nm 3 / h to 200Nm 3 / h, or 30Nm 3 / h to 150Nm 3 / h. Temperatures of about 2000°C can be reached inside the reactor by incomplete combustion of the hydrocarbon feedstock. Typically, acetylene black is formed in the reactor at a temperature of at least 1700°C, such as above 1800°C, or above 1900°C, or above 2000°C.

[0037] For safety and process control reasons, the pressure in the reactor can be controlled during operation. The pressure in the reactor can be higher than atmospheric pressure (101.3 kPa) to prevent air from entering. For example, the pressure in the reactor can be in the range of 0.01 MPa to 1 MPa higher than atmospheric pressure. Alternatively, the reactor may also be operated under vacuum, i.e., at a pressure lower than atmospheric pressure, for example, at a pressure in the range of 1 kPa to 100 kPa.

[0038] like Figure 1As shown, a process for manufacturing acetylene black according to the present invention can be carried out in a reactor. The reactor includes a vertical furnace (1). For example, the vertical furnace (1) can be, for example, a vertical cylindrical furnace with a total height of 7.4m and an inner diameter of 300mm. A burner (2) is provided at the upper part of the vertical furnace. An oxygen-containing gas (e.g., air) can be supplied from a source (not shown) to an optional preheater (5) (which can be optionally preheated) via a feed line (9), and then transferred to the burner (2) via a pipeline (11). A hydrocarbon feedstock containing acetylene can be supplied from a source (not shown) to an optional preheater (4) (which can be optionally preheated therein) via a feed line (8), and then transferred to the burner (2) via a pipeline (10). Optionally, a device for measuring the temperature of the oxygen-containing gas (13) supplied to the burner and the temperature of the hydrocarbon feedstock (12) can be provided. In operation, the oxygen-containing gas and the hydrocarbon feedstock are introduced into the vertical furnace (1) via the burner (2). The amounts of oxygen-containing gas and hydrocarbon feedstock are adjusted so that the molar ratio of oxygen to acetylene has a desired value. The burner (2) can be configured so that the oxygen-containing gas stream is introduced into the furnace (1) and the introduction zone is adjacent to the introduction zone of the hydrocarbon feedstock stream, for example at its edge and approximately tangentially thereto. The burner (2) can, for example, comprise an axial nozzle provided with a cylindrical inner passage for introducing the hydrocarbon feedstock containing acetylene, the cylindrical inner passage being surrounded by a hollow annular region for introducing the oxygen-containing gas. Such a burner is described in more detail in, for example, US4013759. The burner can comprise cooling means, for example water cooling of the acetylene inlet pipe, which can minimize acetylene polymerization and thereby reduce coking, as described, for example, in a paper entitled "The production of carbon black by the thermal decomposition of acetylene and acetylene-hydrocarbon mixtures" published by EJ Claassen Jr in Austin, Texas in May 1948. Incomplete combustion of the hydrocarbon feedstock occurs in the combustion zone at the top of the vertical furnace (1). As described in the above-mentioned paper by EJ Claassen, unwanted coking can be delayed by premixing the acetylene with the hydrogen and / or ensuring that the acetylene is ejected very quickly from the burner nozzle. The walls of the vertical furnace or parts thereof (e.g. in the upper part of the furnace) can be protected from the high temperatures occurring in the furnace by an internal lining with a refractory material (e.g. graphite) and / or by being provided with a cooling device (e.g. a water-cooled jacket) (14). Thus, it is also possible to increase the reaction temperature and / or the yield. A pressure gradient is generated in the furnace by means of a pump or ventilator (3).The aerosol formed by the reaction, containing the formed acetylene black particles and residual gases, is extracted in the lower part of the vertical furnace (1) through a circuit (17), along which the aerosol is cooled by natural convection. A device for measuring the temperature of the aerosol (16) extracted from the vertical furnace can be installed along the circuit (17). The cooled aerosol is directed through the circuit (17) to one or more cyclones (7) for separating the formed acetylene black from the gases of the aerosol. The separated acetylene black is then collected in a container, for example a hopper (15), while the gases separated by the cyclone separator are discharged.

[0039] In operation, the hydrocarbon feed stream may be interrupted from time to time for a short period of time (e.g., a few seconds to a minute), during which a pressurized gas stream (e.g., compressed air) is fed to the furnace to dislodge carbon black that may have deposited on the burners or furnace walls. A crusher (6) may be provided at the bottom of the vertical furnace for breaking up agglomerates of carbon black that may have dislodged from the burners or furnace walls.

[0040] From time to time (e.g., days to weeks) the reactor may be taken out of production for a short period of time and cleaned after it has cooled down. This cleaning removes all deposits and is more thorough than the on-the-fly cleaning described previously. Cleaning can be achieved with high-pressure air, brushes, ultrasonic cleaning equipment, and other common cleaning aids.

[0041] Optionally, the reactor may also include a device for separating grit from the aerosol, such as a wire grid filter made of a material that can withstand high operating temperatures (e.g., a nickel-based alloy). As another option, the reactor may include one or more purification devices (e.g., a magnetic filter) for removing impurities such as metal or metal-rich particles from the aerosol. Optional devices for separating grit and / or purification devices may be provided, for example, along the loop (17).

[0042] The acetylene black formed according to the above-mentioned manufacturing method is usually obtained in the form of fluffy powder. The obtained powder can be further processed, if necessary, such as particle size classification (such as by using a sieve) and / or densification. For example, the acetylene black obtained in the form of fluffy powder can be densified to form a compacted entity (compacted entity) that can be obtained therefrom, such as pellets (pellets), particles (granules) or the like. Densification can be carried out by any method known in the art for densification of powdery materials, such as but not limited to application of vacuum, pressing (pressing), calendering (rolling), granulation (pelletizing), granulation (granulation), briquetting or their combination. The densification of acetylene black can be carried out using conventional techniques and equipment, including such as fluidized bed spray granulation, fluidized spray drying, agitation granulation, dry granulation, wet granulation or their combination. The granulation of initial acetylene black can be carried out such as described in EP2913368B1. Acetylene black can be optionally further dried, especially when acetylene black contacts with wet medium, for example in wet granulation step.Drying can be carried out by drying method commonly used in this area, for example by heating and / or vacuum.For example, acetylene black can be dried so that the residual moisture content of acetylene black (for example dense acetylene black) after drying is less than 0.1 % by weight, for example less than 0.05 % by weight based on the gross weight of acetylene black.Moisture content can be determined according to ASTM D1509-95.

[0043] Acetylene black according to the present invention, which can be obtained, for example, as described above, can be used in various technical applications, including various types of applications in which acetylene black is commonly used. For application, acetylene black can be compounded with one or more other components (e.g., adhesives and / or solvents), as described in more detail below. Therefore, the present invention also relates to a composition comprising acetylene black as described herein. In this article, acetylene black according to the present invention can impart an abnormally high electrical conductivity and / or thermal conductivity to a composition or article made therefrom, and / or allow the electrical conductivity and / or thermal conductivity of a desired level to be imparted to it when the concentration of acetylene black is relatively low.

[0044] Acetylene black of the present invention can be advantageously processed using common powder processing techniques and equipment, and can be easily made into compositions. The compositions can be provided in the form of, for example, dispersions, dry powders, pastes or solids. Acetylene black materials according to the present invention can be, for example, compounded with carrier media (for example, aqueous or organic solvent-based carrier media or plastic materials) or dispersed in carrier media (for example, aqueous or organic solvent-based carrier media or plastic materials). For this purpose, common mixing and stirring equipment can be used, such as agitators, mixers, kneaders, single screws or twin screw extruders. Acetylene black according to the present invention usually shows good dispersibility in various carrier media, and produces compositions with suitable and stable processing and application performance. Wherein the consumption of powdery acetylene black material depends to a great extent on the type of composition and the expected application type, and can be selected by those skilled in the art based on a formula similar to conventional acetylene black according to respective needs.

[0045] As used herein, aqueous carrier medium refers to a carrier medium comprising more than 50% by weight of water, such as 70% by weight or more, or 80% by weight or more, or 90% by weight or more, or up to 100% by weight of water, based on the total weight of the carrier medium. An organic solvent-based carrier medium refers to a carrier medium comprising more than 50% by weight of an organic solvent, such as 70% by weight or more, or 80% by weight or more, or 90% by weight or more, or up to 100% by weight of an organic solvent, based on the total weight of the carrier medium. The type of carrier medium used depends on the corresponding application type and may vary greatly. The carrier medium may include water and / or one or more organic solvents. Organic solvents that can be used include, for example, but are not limited to, alcohols, ketones, aldehydes, amines, esters, ethers, carboxylic acids, hydrocarbons, or mixtures or combinations thereof.

[0046] Similarly, all types of polymeric or resinous materials may be used as plastic material or binder in the composition according to the invention, depending on the intended application. Non-limiting examples of useful resins and polymers that can be used according to the present invention include olefin polymers (e.g., polypropylene, polyethylene, ethylene-vinyl acetate copolymers, ethylene-vinyl alcohol resins, cyclic olefin copolymers), rubbers (e.g., natural rubber, styrene-butadiene rubber, nitrile rubber, butyl rubber, acrylic rubber, ethylene-propylene rubber, ethylene-propylene diene rubber, ethylene-α-olefin copolymer rubber, silicone rubber, fluororubber, chloroprene rubber, alcohol rubber, and chlorosulfonated polyethylene rubber), vinyl chloride polymers (e.g., polyvinyl chloride and ethylene vinyl chloride copolymers), styrene polymers (e.g., polystyrene, styrene-acrylonitrile copolymers, and acrylonitrile-butadiene-styrene copolymers), acrylic polymers (e.g., polymethyl methacrylate), polyesters (e.g., polyethylene terephthalate, polybutylene terephthalate, polyamides, polyacetals, polycarbonates, polyphenylene oxides), fluorine-containing polymers (e.g., polytetrafluoroethylene and polyvinylidinefluoride), polyphenylene sulfides, liquid crystal polymers, thermoplastic polyamides, ketone-type resins, The present invention also relates to rubber or plastic compositions comprising acetylene black as disclosed herein and a rubber or polymer (a rubber or polymer as described above). It also relates to rubber and plastic products made from these rubber or plastic compositions.

[0047] According to the type of application, other ingredients can be used in the preparation of the composition according to the present invention. Those skilled in the art will select these optional other ingredients and their respective amounts according to the expected performance and / or application of the composition. The illustrative examples of these other ingredients include, for example, oil and wax, processing aid, rheology modifier, pH modifier, filler, pigment, dye, coupling agent, catalyst, accelerator, vulcanizing agent, activator, sulfur curing agent, antidegradant, antioxidant, stabilizer, biocide and plasticizer. As described in more detail below, the composition according to the present invention can be used for electrochemical applications, such as battery applications. For these applications, they can also include one or more electrochemically active ingredients accordingly. Electrochemically active ingredients can be, for example, common negative electrode materials (anode material) or positive electrode materials (cathode material).

[0048] It will be understood that acetylene black according to the present invention and compositions comprising it and articles made therefrom can be particularly suitable for applications requiring or being beneficial to high electrical conductivity and / or thermal conductivity. Acetylene black material of the present invention can, for example, impart electrical conductivity to compositions containing the material and articles made therefrom. Therefore, acetylene carbon black material according to the present invention is particularly suitable for, for example, electrodes, conductive catalyst carriers and conductors (including high-voltage cables, and power supplies and battery applications (including primary cells, secondary cells, fuel cells and capacitors)). Therefore, the present invention further relates to electrodes or other components of energy storage and / or conversion equipment made from acetylene black of the present invention or compositions comprising the acetylene black. The present invention also relates to energy storage and / or conversion equipment comprising such electrodes or components. Energy storage and / or conversion equipment can, for example, be primary cells, secondary cells, fuel cells and capacitors. In addition, acetylene black material of the present invention and compositions containing the acetylene black material and articles made therefrom can be used as thermally conductive materials or heat transfer materials or for producing thermally conductive materials or heat transfer materials.

[0049] In addition, acetylene black materials may also be used as antistatic agents or conductive agents, for example, in rubber or plastic materials and articles such as air bags used in the production of tires.

[0050] Acetylene black as disclosed herein can be used, for example, as a conductive agent, antistatic agent, thermal conductor, reinforcing filler and / or colorant, for example, in the production of electrodes and other components of energy storage devices and / or energy conversion devices (e.g., primary cells, secondary cells, fuel cells and capacitors), and / or plastic products made of thermoplastic or thermosetting polymers or rubber matrices (e.g., tires, wire and cable sheathing, belts, hoses, shoe soles, rollers, heaters or airbags (e.g., tire airbags), thermal conductive materials, heat transfer materials), and / or in coatings, paints or inks.

[0051] The present invention has been generally described above, and further understanding can be obtained by referring to the following specific examples. These examples are provided herein for illustrative purposes only and are not intended to limit the present invention, which shall be given the full scope of the appended claims including any equivalent schemes thereof.

[0052] Example

[0053] Preparation of acetylene black

[0054] As mentioned above, acetylene black is produced in the reactor, which is Figure 1Schematically described in . The reactor comprises a vertical furnace (1) with a burner (2), the top of which extends to the furnace. Acetylene and air are supplied to the axial nozzle of the burner respectively through a supply line (8) and a supply line (9). A preheater (5) is installed in the air supply line to preheat the air feed. No preheater (4) is used in the acetylene supply line. In the vertical furnace, incomplete combustion of the supplied acetylene is carried out by the supplied air, resulting in the formation of acetylene black. The furnace wall is protected from the high temperature in the furnace by a double-layer water cooling jacket (14). A ventilator (3) connected to the fluid of the lower part of the furnace causes a pressure reduction in the furnace to prevent the burner from clogging, and the formed aerosol containing acetylene black is guided through a loop (17) (where it is cooled due to natural convection) to a group of cyclones (7) (where acetylene black is separated from the gas and collected in a container).

[0055] Example 1

[0056] Using the above reactor, 42Nm 3 / h acetylene (not preheated) and 75Nm 3 / h of air (preheated to a temperature of 300°C) is introduced into a vertical furnace to produce acetylene black. Every 60 minutes, the acetylene flow is interrupted and a cleaning cycle of about 2 minutes is started, which uses air compressed to 2 bar at normal temperature. The acetylene flow is then started again. The acetylene black thus obtained is collected in the hopper (15) of the reactor. The stoichiometric yield is 58%.

[0057] Example 2 (Comparative Example)

[0058] Another acetylene black was produced using the above reactor. The operation was carried out as in Example 1, but 55 Nm 3 / h acetylene (not preheated) and 75Nm 3 / h of air (preheated to 300° C.) is introduced into the vertical furnace. Every 60 minutes, the acetylene flow is interrupted and a cleaning cycle of about 2 minutes long is started, which uses air compressed to 2 bar at normal temperature. The acetylene flow is then started again. The acetylene black thus obtained is collected in the hopper (15) of the reactor. The stoichiometric yield is 66%.

[0059] Acetylene black properties

[0060] The properties of the acetylene black obtained according to Examples 1 and 2, as determined according to the characterization method proposed below, are summarized in Table 1, compared with acetylene black commercially available from Denka Co. Ltd. under the trade name "Li-435" as a reference material, which is used as a conductive agent in the art.

[0061] As can be seen from Table 1, the acetylene black material according to the present invention (Example 1) in particular has a significantly higher structure (indicated by a higher OAN and void volume) and exhibits a significantly lower volume resistivity, i.e., a higher conductivity than the comparative acetylene black material according to Comparative Example 2 or the commercial reference material Li-435.

[0062] [Table 1]: Properties of acetylene black

[0063]

[0064] BET surface area was measured by nitrogen adsorption according to ASTM D6556-19a. The pressure points applied were 0.05, 0.075 and 0.1 p / p 0 . The amount of sample used ranges from 0.15 g to 0.4 g. Prior to BET analysis, the powdered carbon black sample is compressed. To this end, 5 g of the powdered carbon black sample is added to a paper bag. The closed paper bag is then inserted into a plastic zipper bag. The zipper bag is then closed, leaving a small opening where an assembly tube connected to a vacuum pump is inserted. The vacuum pump is then turned on and the tube is placed on the edge of the paper bag in the plastic zipper bag. The zipper bag is then tightly closed and the enclosed air pockets are manually removed. Compression is then further performed under vacuum for 60 seconds. The vacuum is then turned off and the compressed carbon black sample is removed from the paper bag.

[0065] The oil absorption number (OAN) was measured according to ASTM D2414-19 Method B. The amount of carbon black sample used ranged from 6 g to 12 g.

[0066] Carbon content, oxygen content, nitrogen content and sulfur content were measured by elemental quantitative analysis using an automatic elemental analyzer (vario EL cube elemental analyzer purchased from Elementar Analysensysteme GmbH) according to DIN 51732-2014-07. Prior to elemental quantitative analysis, the acetylene black material to be analyzed was dried at 125° C. for 2 hours.

[0067] The particle diameter, shape and form of acetylene black are studied by TEM analysis.20mg of acetylene black material to be analyzed is transferred in 5ml polyethylene experimental tube, and in ultrasonic bath (using ultrasonic rod immersed in bath and running under the power of 100W), in 2mL chloroform, disperse 3 minutes to provide the good dispersion liquid of acetylene black powder.Afterwards, a drop of dispersion liquid is transferred to the copper TEM carrier grid (200 orders) that scribbles carbon coating with Ai Bende microliter pipette (Eppendorf Microliter pipette).Then the carrier grid (loaded grid) that has loaded sample is transferred to the high vacuum of TEM instrument (Hitachi (Hitachi) H-7500, 100kV) and studied.According to ASTM D3849-07, from one group of representative TEM images that comprise about 2000 well-dispersed separated particles, determine average primary particle size by automatic image analysis.

[0068] The size distribution of aggregates was further determined by Disc Centrifugal Particle Sizer (DCP) according to ISO 15825:2017 for the acetylene black studied using a Brookhaven BI-DCP particle size analyzer.

[0069] The acetylene black material was further analyzed by Raman spectroscopy. For this purpose, a powder sample of the acetylene black material to be analyzed was placed on a microscope slide and flattened by gently pressing it manually from the top with a second microscope slide. The Raman spectra of the samples thus prepared were then recorded using a Thermo Scientific DXR Raman microscope (Thermo Fisher Scientific), which had a 50x magnification, a laser power of 0.5 mW, a wavelength of 532 nm, a collection time of 2 seconds, and an exposure rate of 32. For each sample, measurements were taken at 10 different locations to verify repeatability. The peak fitting analysis determined the peaks at about 1360 cm from the recorded Raman spectra. -1 The intensity of the defect band (D band) at about 1580 cm -1 The intensity of the graphite band (G band) at . The reported (D / G) ratio corresponds to the arithmetic mean of the ratio of the D band intensity to the G band intensity in the ten measurements performed. Lower values ​​of the (D / G) ratio indicate a relatively high proportion of graphitic domains, i.e. a higher degree of order / crystallinity.

[0070] In addition, the acetylene black material was analyzed by X-ray diffraction (XRD) to determine its crystallite size L using the method described in "Self-decomposition of hydrogen peroxide on the surface of dispersed carbon black" GI Razdyakonova, VA Likholobov, Nanosystems, RENSIT, 2015, 7(2):180-190. a and grain size L c .

[0071] Determine the void volume according to ASTM D7854-18a. To this end, the acetylene black sample to be analyzed is placed on a tray and dried in a convection oven set to 125 ± 5 ° C for at least one hour. The dried material is then cooled to ambient temperature and stored in a desiccator before use. Using a balance, 1.000g of the sample is accurately weighed to 0.1mg and placed in a sample tray. The weighed sample is then transferred to a cylindrical sample chamber (1 inch in diameter) of a void volume measuring instrument (CVST of Luxembourg Hitec) using a funnel. Carefully brush the sample tray and funnel to ensure that all samples are introduced into the cylindrical sample chamber. The cylindrical sample chamber is then closed, and the test is started by applying pressure to the movable piston of the cylindrical sample chamber, and the compressed volume of the weighed sample in the cylindrical chamber is measured, which is a function of the pressure applied by the movable piston. The pressure was increased from 0 to 125 MPa geometric mean pressure and then decreased from 125 MPa to 0 MPa geometric mean pressure at a compression / decompression rate of 2 MPa / s. The compression and decompression curves were recorded and the void volume was calculated from the measured volumes as a function of the pressure applied by the movable piston and the weight of the sample. The values ​​reported in Table 1 correspond to the arithmetic mean of the void volumes determined in the compression and decompression curves at a geometric pressure of 50 MPa, 75 MPa or 125 MPa, respectively.

[0072] The powder resistivity of acetylene black was measured simultaneously with the above-mentioned void volume test using a void volume meter (CVST, HITEC, Luxembourg) with a ceramic cylindrical sample chamber according to the manufacturer's instructions. The electrical resistance of the analyzed sample was recorded in the compression scan and the decompression scan as a function of the pressure applied by the movable piston, from which the resistivity was calculated. The values ​​reported in Table 1 correspond to the arithmetic mean of the resistivities determined at a geometric mean pressure of 50 MPa in the compression curve and the decompression curve.

[0073] Preparation of electrode slurry

[0074] A dry premix was prepared by adding 4.5 g of Solef 5130 (Solvay) PVDF polymer, 291 g of lithium nickel manganese cobalt oxide NMC 532 (BASF) and 4.5 g of acetylene black or Li-435 according to Example 1 to the mixing vessel of a double planetary mixer (FMPE HM2P-03 model from Bühler Technologies GmbH, Ratingen, Germany). The dry composition was mixed in the double planetary mixer at a speed of 20 rpm for 15 minutes at room temperature.

[0075] Next, the premix was dispersed in an organic solvent in a two-step procedure. First, 80 g of N-methyl-2-pyrrolidone (NMP, analytical grade ≥99.5%, provided by VWR Chemicals) and 1.125 g of a dispersant (BYK 40% LPN24711) were added to the respective premixes, followed by mixing at 40 rpm for 10 minutes in a double planetary mixer, followed by mixing at 80 rpm for 50 minutes. Subsequently, an additional 5 g of NMP was added to the mixture, and the composition was mixed at 80 rpm for another 20 minutes in a double planetary mixer to obtain an electrode slurry. The fineness of the slurry measured with a Hagman gauge was less than 20 µm.

[0076] Preparation of electrode films and measurement of resistivity

[0077] The electrode film was prepared from the prepared electrode slurry within 4 hours of its preparation. The cathode film was prepared according to the following steps: A 20 µm thick aluminum foil used as a current collector was placed steadily and firmly on a coater (K ​​control coater from TQC Sheen). The corresponding electrode slurry was then applied to one side of the aluminum foil, and the layer thickness was adjusted using the coater's doctor blade with a gap of 200 µm. The coated electrode was dried in a vacuum oven at 100 °C for 3 hours.

[0078] The resistance of the electrode film thus obtained was measured with a HIOKI 4-terminal probe of the RM 3543-01 resistance meter HiTESTER purchased from HIOKI Electric Co., Ltd. (HIOKI). To this end, the corresponding coated aluminum foil was cut into a disc shape with a diameter of 14 mm, and the front and rear surfaces were sandwiched between two flat plated metering electrodes (flat plated meteringelectrode) (diameter: 10 mm, surface area: 0.7854 cm²). Pre-testing was performed during equipment preheating and zero point calibration using a copper disc. The measuring range was set to 1000 mΩ. After conditioning for 40 seconds at an applied pressure of 0.4 MPa, the resistance value was automatically read from the HIOKI device. The volume resistivity was calculated by multiplying the obtained resistance value by the measured area of ​​the plate-shaped measuring electrode (0.7854 cm²) and then dividing it by the measured electrode coating thickness. The tabulated results shown in Table 2 below represent the arithmetic mean of 6 disc samples from the same coating.

[0079] [Table 2] Average electrode volume resistivity of electrodes prepared from electrode slurries containing different acetylene blacks

[0080]

[0081] As can be seen from Table 2, the electrode formed from the slurry containing the acetylene black material according to the present invention (Example 1) exhibits significantly lower resistivity than the electrode derived from the commercial reference material Li-435.

Claims

1. An acetylene black having (a) an oil absorption value (OAN) of 360 mL / 100 g or more as measured according to ASTM D2414-19 and (b) an oil absorption value (OAN) of 50 mL / 100 g or more as measured according to ASTM D6556-19a. 2 / g to 200m 2 / g of BET surface area. 2 . The acetylene black according to claim 1 , wherein the OAN of the acetylene black is 380 mL / 100 g or more, for example, in the range of 380 mL / 100 g to 500 mL / 100 g.

3. The acetylene black according to any one of claim 1 or claim 2, wherein the BET surface area of ​​the acetylene black is 80 m 2 / g to 160m 2 / g range.

4. The acetylene black according to any one of the preceding claims, having an L of 26 Å or more as measured by X-ray diffraction. c The crystallite size is, for example, in the range of 28 Å to 40 Å, and / or has an L of greater than 60 Å as measured by X-ray diffraction. a The grain size is, for example, in the range of 70Å to 90Å.

5. Acetylene black according to any one of the preceding claims, having a D / G ratio measured by Raman spectroscopy of less than 1.5, for example in the range of 1.0 to 1.

5.

6. The acetylene black according to any one of the preceding claims, having a D mode In the range of 50 nm to 200 nm and / or the ratio ΔD50 / D mode Agglomerate particle size distribution in the range of 0.5 to 2.

5.

7. Acetylene black according to any one of the preceding claims, having one or more or all of the following: - a carbon content of at least 99.0% by weight, for example at least 99.5% by weight, - an oxygen content of less than 0.1 wt. %, for example less than 0.05 wt. %, - a hydrogen content of less than 0.5% by weight, for example less than 0.3% by weight, - a sulfur content of less than 0.1% by weight, preferably less than 0.05% by weight, - a nitrogen content of less than 0.2% by weight, preferably less than 0.1% by weight, - A metal content of less than 1000 ppm, preferably less than 100 ppm, or less than 50 ppm, or less than 20 ppm or less than 10 ppm.

8. The acetylene black according to any one of the preceding claims, having a 70 cm 3 / 100g or more void volume, preferably 75cm 3 / 100g or more, and / or has a powder resistivity of less than 0.1Ω·cm, preferably less than 0.06Ω·cm, measured under a pressure of 50 MPa.

9. A method for producing acetylene black according to any one of claims 1 to 8, the method comprising: providing a hydrocarbon feedstock comprising acetylene to a reactor, providing an oxygen-containing gas to the reactor, achieving incomplete combustion of the hydrocarbon feedstock containing acetylene by contacting the hydrocarbon feedstock containing acetylene with the oxygen-containing gas, thereby forming acetylene black in the reactor, and Recovery of the acetylene black formed, The hydrocarbon feedstock containing acetylene and the oxygen-containing gas are introduced into the reactor such that a molar ratio of oxygen to acetylene is in the range of 0.30 to 0.

80.

10. A composition comprising the acetylene black according to any one of claims 1 to 8.

11. The composition of claim 10, further comprising at least one of an electrochemically active component, a binder, and a solvent.

12. An electrode or other component of an energy storage and / or conversion device made from the acetylene black according to any one of claims 1 to 8 or the composition according to any one of claims 10 or 11.

13. An energy storage and / or conversion device comprising an electrode or assembly according to claim 12.

14. A rubber or plastic article made from the composition according to any one of claims 10 or 11, the composition comprising acetylene black according to any one of claims 1 to 8 and at least one rubber or polymer.

15. Use of the acetylene black material according to any one of claims 1 to 8 as a conductive agent, an antistatic agent, a thermal conductive agent, a reinforcing filler and / or a colorant.

Citation Information

Patent Citations

  • Pelleted acetylene black

    EP2913368B1

  • Acetylene-like black and process

    US4013759A